The exports from the western Balkans countries to the EU: The main problems and recommendations - Ćulahović Besim (Ekonomski Anali, 2006)
The European Union (EU) trade policy towards Western Balkan's countries (Albania, Bosnia-Herzegovina, Croatia, Serbia and Montenegro and the Republic of Macedonia) is one of the important tools of EU's integration strategy. The exports from the Western Balkan’s countries to the European Union(15) are preferred within special autonomous trade measures for the Western Balkan’s countries which were introduced by the EU in September 2000 (the 2000TM). The 2000TM are a far-ranging set of preferences which provide the Western Balkan’s countries with unparalleled market access to the EU, and hence with the potential both to develop the existing exports and to generate new exports. However, the Western Balkan’s countries exports to the EU are far below the level which could reasonably be expected. In all Western Balkan’s countries a number of supply-side and domestic policy reasons are identified for this under-performance, which suggests that the 2000TM are likely in part to rectify the situation. The economic regeneration of the Western Balkan’s countries will depend on the success of internal economic reform and on the adoption of economic and trade policies which specifically identify and address some serious supply-side constraints.